Sinkronisasi Kebijakan Alur Laut Kepulauan Indonesia Terhadap Standar Keselamatan Pelayaran Internasional - Septiu Dicke Davis; M. Fikri Nofriyansyah; Fathurrahman Isnanda; Muhammad Hidayatullah (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
This study examines the synchronization of Indonesia’s Archipelagic Sea Lanes policy with international shipping safety standards. ALKI serves as a strategic route for foreign vessels and aircraft exercising the right of archipelagic sea lanes passage under UNCLOS 1982. However, national regulations still place greater emphasis on passage rights, foreign vessel obligations, and the protection of state sovereignty, while shipping safety aspects have not been regulated in an integrated manner. This study uses a normative legal method with statutory and conceptual approaches. The legal materials analyzed include UNCLOS 1982, SOLAS 1974, COLREG 1972, the SAR Convention 1979, IMO standards, and relevant national regulations on ALKI. The findings show that ALKI policy needs to be strengthened through the synchronization of norms on navigational safety, collision prevention, ship reporting systems, vessel traffic services, search and rescue, and inter-agency coordination. This synchronization is essential so that ALKI does not merely function as an international passage route, but also as a legal instrument to ensure shipping safety, protect sovereignty, and preserve Indonesia’s marine environment.